Domestic violence in Asia globalization, gender and Islam in the Maldives - Fulu, Emma (Asian Studies Association of Australia women in Asia series, 2014)
"Explores changing patterns of domestic violence in Asia. Based on extensive original research in the Maldives, it argues that forces of globalisation, consumerism, Islamism and democratisation are changing the nature of domestic relations, with shifting ideas surrounding gender and Islam being particularly significant"--Provided by publisher.